Army Dock, Konstruksi Bangunan Pendaratan Sekutu Pada Perang Pasifik di Pulau Morotai : Army Dock, an Allies Landing Building Construction on Pacific War in The Morotai Island - Deni Sutrisna (Kemendikbud, 2021)
The Pacific War, it is a sad history of humanity for most people, especially war veterans. Their stories passed on to the younger generation, many stories and tales were recorded: starting from preparations for war, war strategies, the course of war and the liberation of a colony from invaders is interesting to listen to. Army dock is one of the remnants of the Pacific War on Morotai Island which is an important part of the history. It’s existence not only describes the Allies landing process to liberate the island from Japanese rule, it is also a historical source of Indonesia's involvement in the Pacific War arena. It is possible, because the Allies and the Japanese took advantage of the natural resources of Morotai Island to build various infrastructure needed for war, including the Army dock. The army dock was built composition of building materials by utilizing existing materials in the coastal areas of the island, namely limestone reef. This initial step of the Allies strategy finally succeeded in liberating Morotai Island from Japanese occupation, from here later grew the construction of other military facilities and infrastructure that were built to prepare to retake the Philippine island of Mindanao, the largest military base outside Japan. How the Army dock was built and its function in the past, is a problem that will be answered in this paper. In order to answer these problems, the observation method is used through field surveys and library data searches.